(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article contains information about investigation of effectiveness of teaching English by using deductive and inductive approaches of teaching grammar. The investigation also attempts to see which of these two methods has a positive effect on the grammar academic achievement of the secondary school pupils, so it answers to the following questions: What are inductive and deductive approaches of teaching grammar? What advantages and disadvantages they have got? What is the effect of inductive method on grammar achievement compared to deductive method at secondary school? · What is the effect of inductive method on grammar achievement compared to deductive method at secondary school? To answer the questions of the study, the researcher has made research based on inductive and deductive methods for each level based on its syllabus. The sample consists of 58 pupils. 30 pupils in the 6th grade and 28 pupils in the 11th grade. They are the pupils who study in specialized groups on English, at secondary school number 2 of Samarkand district. Firstly, pupils were divided into two groups. The pupils of the 1st group were selected and assigned to be taught by using inductive approach, when the pupils of the 2nd group were selected and assigned to be taught by using deductive approach. The relevant pre-tests were prepared to the pupils of both groups just to make sure that the groups are equal at the time of starting the experiment. The researcher designed two grammar achievement tests as the instruments of this study. The instrument of each group consists of two achievement tests (pre-test and post-test). At the end of the treatment period, relevant post-tests were made to the pupils of both groups. The results of the study revealed that there were significant statistical differences among the grammar performance means of both groups at both levels due to inductive method.